Key questions for decision-makers: Protection of plant varieties under the WTO agreement on trade-related aspects of the intellectual property rights. Decision tools - International Plant Genetic Resources Institute (1999)
Today's decision-makers are faced with implementing a myriad of international legal obligations that are relevant to the conservation, use and development of plant genetic resources. These obligations arise from international legal treaties and instruments with diverse and – if not implemented rationally – potentially conflicting objectives. These include, for example, liberalizing trade, conserving wetlands, conserving biodiversity and ensuring equitable benefit-sharing derived from its sustainable use, and mitigating the effects of, and ultimately halting, climate change. IPGRI's legal and policy work aims to provide decision-makers with practical analysis and tools to guide them in formulating responsive policy and legislation that is consistent with their national objectives and the sustainable management of plant genetic resources. This volume is part of an ongoing body of work that IPGRI hopes will assist decision-makers with the complex task of discerning the many issues of relevance to the conservation and management of plant genetic resources and devising a coherent and consistent policy and legislative response. It is our hope that decision-makers and those wishing to influence the decision-making process will find this volume to be a useful tool to help understand implementation options under Article 27.3(b) of the TRIPs Agreement and their potential implications for their country's objectives relevant to plant genetic resources.